1985
DOI: 10.1210/jcem-60-6-1210
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Epinephrine and Norepinephrine in Man*

Abstract: The diurnal rhythms of plasma epinephrine and norepinephrine were investigated in a group of normal young men. Sleep, posture, illumination, and food intake were monitored. Plasma epinephrine demonstrated a statistically significant diurnal rhythm, with a mean amplitude of 14 +/- 1.6 (+/- SE) pg/ml superimposed on a mean level of 43 +/- 5.3 pg/ml. The trough occurred at 03.20 h +/- 35 min. Plasma norepinephrine had a significant diurnal rhythm, with a mean amplitude of 111 +/- 19 pg/ml superimposed on a mean l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
175
2
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(186 citation statements)
references
References 20 publications
8
175
2
1
Order By: Relevance
“…However, few studies have standardized behavioral and environmental factors across the day/night cycle, which is a requirement to separate endogenous circadian from behavioral/ environmental effects (e.g., induced by the daily rest/activity cycle). Linsell et al (26) had indirect evidence of a circadian rhythm in plasma epinephrine (but not norepinephrine) based on 24-h fluctuations in epinephrine that could not be fully explained by sleep and/or posture. No daily rhythm in plasma or urinary epinephrine was found in a study in which subjects remained supine, but sleep/wake, feeding, and lighting conditions were not strictly controlled (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have standardized behavioral and environmental factors across the day/night cycle, which is a requirement to separate endogenous circadian from behavioral/ environmental effects (e.g., induced by the daily rest/activity cycle). Linsell et al (26) had indirect evidence of a circadian rhythm in plasma epinephrine (but not norepinephrine) based on 24-h fluctuations in epinephrine that could not be fully explained by sleep and/or posture. No daily rhythm in plasma or urinary epinephrine was found in a study in which subjects remained supine, but sleep/wake, feeding, and lighting conditions were not strictly controlled (27).…”
Section: Discussionmentioning
confidence: 99%
“…29 Besides the circadian blood pressure pattern, increasing numbers of studies indicate that cardiovascular events occur more frequently in the morning, and that this phenomenon may be related to the morning blood pressure surge. 30 An anti-hypertensive medication that reduces the morning blood pressure surge would be useful in the prevention of cardiovascular events in hypertensive patients. The present study, the first prospective randomized trial to focus on a fixed combination of two anti-hypertensive medicines, found that similar to the chronotherapy studies of single medications, administration of amlodipine complex at bedtime significantly minimizes the morning surge, lowers the nocturnal blood pressure, increases the diurnal/ nocturnal ratio of blood pressure and reduces the number of nondipper patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the precise mechanisms by which morning hypertension occur are not fully understood. However, abnormalities such as an increase in sympathetic nerve activity (23), excessive activity of RAS (24), and a hypercoagulable and hypofibrinolytic state may be involved in the process (25). Recently, Kamoi et al demonstrated that elevations of HBP in the morning in patients with diabetes are strongly related to microvascular and macrovascular complications, especially nephropathy, suggesting that the control of HBP in the morning is crucial to prevent further progression of the kidney (12).…”
Section: Morning Hypertension and Organ Damagementioning
confidence: 99%